CDC174, a novel component of the exon junction complex whose mutation underlies a syndrome of hypotonia and psychomotor developmental delay. (10th September 2015) - Volodarsky, Michael; Lichtig, Hava; Leibson, Tom; Sadaka, Yair; Kadir, Rotem; Perez, Yonatan; Liani-Leibson, Keren; Gradstein, Libe; Shaco-Levy, Ruthy; Shorer, Zamir; Frank, Dale; Birk, Ohad S.
Abstract : Siblings of non-consanguineous Jewish-Ethiopian ancestry presented with congenital axial hypotonia, weakness of the abducens nerve, psychomotor developmental delay with brain ventriculomegaly, variable thinning of corpus callosum and cardiac septal defects. Homozygosity mapping identified a single disease-associated locus of 3.5 Mb on chromosome 3. Studies of a Bedouin consanguineous kindred affected with a similar recessive phenotype identified a single disease-associated 18 Mb homozygosity locus encompassing the entire 3.5 Mb locus. Whole exome sequencing demonstrated only two homozygous mutations within a shared identical haplotype of 0.6 Mb, common to both Bedouin and Ethiopian affected individuals, suggesting an ancient common founder. Only one of the mutations segregated as expected in both kindreds and was not found in Bedouin and Jewish-Ethiopian controls: c.1404A>G, p.[*468Trpext*6] in CCDC174 . We showed that CCDC174 is ubiquitous, restricted to the cell nucleus and co-localized with EIF4A3. In fact, yeast-two-hybrid assay demonstrated interaction of CCDC174 with EIF4A3, a component of exon junction complex. Knockdown of the CCDC174 ortholog in Xenopus laevis embryos resulted in poor neural fold closure at the neurula stage with later embryonic lethality. Knockdown embryos exhibited a sharp reduction in expression of n-tubulin, a marker for differentiating primary neurons, and of hindbrain markers krox20 and hoxb3. The Xenopus phenotype could be rescued by the human normal, yet not the mutant CCDC174 transcripts. Moreover, overexpression of mutant but not normal CCDC174 in neuroblastoma cells caused rapid apoptosis. In line with the hypotonia phenotype, the CCDC174 mutation caused depletion of RYR1 and marked myopathic changes in skeletal muscle of affected individuals.